Clinical and societal burden of incident major depressive disorder: A population‐wide cohort study in Stockholm. (2nd March 2022) - Lundberg, Johan; Cars, Thomas; Lööv, Sven‐Åke; Söderling, Jonas; Tiihonen, Jari; Leval, Amy; Gannedahl, Anna; Björkholm, Carl; Själin, Mikael; Hellner, Clara
Abstract: Objective: Major depressive disorder (MDD) is a highly prevalent condition and a significant contributor to global disability. The vast majority of MDD is handled by primary care, but most real‐life studies on MDD only include data from secondary care. The aim of this study was therefore to estimate the total clinical and societal burden of incident MDD including data from all healthcare levels in a large well‐defined western European healthcare region. Methods: Population‐wide observational study included healthcare data from Region Stockholm, Sweden's largest region with approximately 2.4 million inhabitants. All patients in Region Stockholm having their first unipolar MDD episode between January 1, 2012, and December 31, 2018, were included. The sample also included matched study population controls. Outcomes were psychiatric and non‐psychiatric comorbid conditions, antidepressant therapy use, healthcare resource utilization, work loss, and all‐cause mortality. Results: In the study period, 137, 822 patients in Region Stockholm were diagnosed with their first unipolar MDD episode. Compared with matched controls, MDD patients had a higher burden of non‐psychiatric and psychiatric comorbid conditions, 3.2 times higher outpatient healthcare resource utilization and 8.6 times more work loss. MDD was also associated with a doubled all‐cause mortality compared with matched controls (HR: 2.2 [95% CI: 2.0–2.4]). Conclusions: The high mortality, morbidity, healthcare resource utilization, and work loss found in this study confirms that MDD is associated with individual suffering and low functioning leading to substantial costs for patients and society. These findings should motivate additional efforts in improving outcomes for MDD patients.